2016
DOI: 10.4103/2249-4863.184629
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics of tobacco users as determinants of tobacco use screening done by healthcare providers: Global Adult Tobacco Survey India 2009-2010

Abstract: Introduction:World Health Organization and Indian Public Health Standards recommend provision of tobacco use screening and cessation help at primary care settings. Evidence shows that brief advice by healthcare provider helps tobacco user quit. It starts with asking the patient about his tobacco use status. The rate of tobacco use screening done by healthcare providers is very low and also depends on sociodemographic characteristics of patients along with several other factors.Objectives:This paper intends to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[ 27 ] The Global Adult Tobacco Survey of 2009 reported that adolescent age group is less likely screened for tobacco use. [ 28 ] This will hamper in developing an age-specific intervention for tobacco cessation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] The Global Adult Tobacco Survey of 2009 reported that adolescent age group is less likely screened for tobacco use. [ 28 ] This will hamper in developing an age-specific intervention for tobacco cessation.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) The prevalence of smoking among women in India is low(0.5% in women Vs 5% in men) (3), possibly due to the prevailing gender norms in many societies including its intersections with other social determinants (like, caste, class, location, and ethnicity) that have shaped sex-based and other differences in tobacco/substance use wherein women generally tend to have lower prevalence of substance use compared to men. (4,5) National Family Health Survey (NFHS-5, 2019-21) data shows around 8.9% of women (above 15 years) use tobacco and 38% of men (above 15 years), while alcohol consumption is relatively 1.3% among women and 18.8% among men. (6) Substance use throughout a person's life is in uenced by a range of factors, starting at an early age.…”
Section: Introductionmentioning
confidence: 99%